TANGGUNG JAWAB CAMAT SEBAGAI PPAT SEMENTARA DALAM HAL MENANDATANGANI AKTA JUAL BELI (CONTOH KASUS NOMOR PUTUSAN 44/PDT.G/2014/PN KWG) - Napoleon Tampubolon; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2018)
The research on the Subdistrict Head's responsibilities as PPAT Temporary aims to know and understand the problems related to legal responsibility if there is an error in making land certificates by the Subdistrict Head as Temporary PPAT and the role of Subdistrict Head who is appointed as Temporary PPAT in the practice of making land deeds in Cibuaya District karawang. This research is normative legal research, namely this research uses scientific methods and interviews with related parties. The data used are primary data, namely regulatory regulations relating to the Occupational Regulation of the Land Deed Maker Officer and secondary data, namely textbooks relating to the Land Deed Maker Officer. In this study the specifications used are prescriptive in nature which are intended to provide prescriptions based on arguments that have been built in conclusions. Head of Subdistrict as PPAT While from Cibuaya Subdistrict, Karawang regency is still making irregularities towards the preparation, manufacture and registration of the deed. The legal responsibility of the mistake made by the Subdistrict Head as a Temporary PPAT in making the land deed is not in accordance with the existing regulations, namely not subject to penalty sanctions in the form of compensation but a decision of the Article of Action Against the Law is imposed.